THE POSITIVE EFFECTS OF PRATIMARSHA NASYA W.S.R. TO SLEEP PHYSIOLOGY - Yadav Kapil*; Kimothi Swati; Kimothi Swati; Bamola Poonam; Goswami Himani; Gupta Himani (AYUSHDHARA, 2019)
Study was planned to preventively deal with sleep disturbances which are waiting to become public health problem. As much as 30% individuals among apparently healthy individuals in India suffer from occasional insomnia. Ayurveda classics offered a solution by use of Pratimarsha Nasya as daily regimen to improve sleep quality. Anu taila is best used for Nasya Karma, so was chosen as medicine for this clinical observational study. Material and methods- 28 subjects were selected randomly and every evening two drops Anu taila in each nostril was administered for 3 months. Result- Significant improvement was found on PSQI, ESS sleepiness scale as well as self developed Sukhnidra Sukhprabodham scale. For self developed sleep quality assessment scale, null scores were present in the enrolled subjects with Baseline mean + SD 0.00 + 0.00 and gradual increase across subsequent intervals. Mean + SD after Trial is 14.54 +1.97. So subjects showed significant response to Pratimarsha nasya with p value <0.0001 and Z value 4.647. Conclusion- Overall sleep quality is more improved after administration of pratimarsha nasya, different components of sleep quality considered viz. getting to sleep, quality of sleep, awake following sleep, behaviour following wakening all are positively changed. Pratimarsha nasya has such a vast positive effect on physiology of sleep that it deserves to be incorporated in daily regimen and can be called as “two drops for well-being of Urdhvajatru”.